Scientific Opinion on the safety and efficacy of Bonvital (Enterococcus faecium) as a feed additive for sows - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2014)
Bonvital is a preparation of a strain of Enterococcus faecium authorised for piglets, pigs for fattening, sows, chickens for fattening, chickens reared for laying and minor poultry species. EFSA was requested to assess the safety and efficacy of Bonvital when used with sows throughout the complete reproductive cycle at the dose of 5 × 108 CFU/kg feed. The safety for the target species, consumers of products derived from animals fed the additive, users and the environment has been considered in the context of the previous opinions. The FEEDAP Panel is not aware of any information that would lead it to revise these conclusions. Consequently, the FEEDAP Panel has considered only the efficacy of Bonvital for sows. The results of three studies each performed over two complete reproductive cycles showed that Bonvital, at the minimum recommended dose of 5 × 108 CFU/kg feed, has the potential to increase litter weight gain or maintain sow condition. Based on these results, the FEEDAP Panel concludes that the data provided support the extension of use of the additive to the entire reproductive cycle.